Pd(ii)-catalyzed β-C–H arylation of O-methyl ketoximes with iodoarenes. Issue 3 (29th January 2016) - Mu, Yucheng; Tan, Xiaodong; Zhang, Yemin; Jing, Xiaobi; Shi, Zhuangzhi
Abstract : A Pd(ii )-catalyzed selective β-arylation of O -methyl ketoximes was developed using iodoarenes as the coupling partners. Abstract : A Pd(ii )-catalyzed selective β-arylation of O -methyl ketoximes was developed using iodoarenes as the coupling partners. This transformation has good functional group compatibility and can serve as a powerful synthetic tool for late-stage C–H arylation of complex compounds. Moreover, when employing 2-iodobenzoic acids as the substrates in this developed catalytic system, a type of unexpected five-membered lactones could be formed by tandem sp 3 C–H arylation and oxygenation.